Heme Oxygenase-1 Protects Hair Cells From Gentamicin-Induced Death - Yang, Yang; Chen, Xin; Tian, Keyong; Tian, Chaoyong; Chen, Liyang; Mi, Wenjuan; Li, Qiong; Qiu, Jianhua; Lin, Ying; Zha, Dingjun (Frontiers in Cellular Neuroscience, 2022)
Gentamicin ototoxicity can generate free radicals within the inner ear, leading to permanent damage to sensory hair cells (HCs) and eventually hearing loss. The following study examined the alterations of oxidative damage-related genes in the cochlea and important molecules responsible for oxidation following gentamicin injury in vitro. The RT² Profiler PCR array was used to screen candidate targets for treatment to prevent hearing loss caused by gentamicin. We found that during gentamicin-induced death in HCs, Heme oxygenase-1 (HO-1) had a high fold change in the HCs of the cochlea. Moreover, the use of CoPPIX to induce HO-1 inhibited gentamicin-induced HC death, while HO-1 inhibitors ZnPPIX after CoPPIX reversed this process. Furthermore, the inhibitors of NF-E2-related factor-2 (Nrf2) reduced the expression of HO-1 and inhibited the protective effect of HO-1 after gentamicin, thus suggesting that the Nrf2/HO-1 axis might regulate gentamicin-associated ototoxicity. We further demonstrated that induction of HO-1 up-regulated the expression of Nrf2 in both cochlear and HEI-OC1 cells. In summary, these findings indicated that HO-1 protects HCs from gentamicin by up-regulating its expression in HCs and interacting with Nrf2 to inhibit ROS.